The Effect of Soft Skills-Based Group Investigation Model on Mathematical Problem Solving Ability and Self- Confidence of Secondary School Student - Ino Rustandi (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
Research indicates that the mathematical problem solving proficiency and self-confidence of Indonesian students, as evidenced by international assessments like PISA and TIMSS, remain areas demanding significant improvement. This situation underscores the critical necessity for an instructional paradigm that concurrently addresses both cognitive and affective development. This investigation aims to analyze the impact of implementing the Group Investigation learning model, integrated with deliberate soft skills reinforcement, on the mathematical problem-solving abilities and self-confidence of secondary high school students. Employing a quantitative methodology, the study involved two purposively selected eighth-grade classes from a public secondary high school in Bandung. Data were gathered using a descriptive test to evaluate problem-solving competency and a Likert scale questionnaire to measure self-confidence levels. Analytical findings revealed a statistically significant enhancement in both measured domains within the experimental group compared to the control group. Participants demonstrated superior conceptual comprehension, a more varied repertoire of solution strategies, and an enhanced capacity for logical justification of their reasoning. The implications of this research highlight the essential role of integrating social and emotional skill development into contemporary mathematics pedagogy. It is, therefore, recommended that educators adopt collaborative instructional strategies that foster an environment conducive to expressing opinions courageously, engaging in metacognitive reflection on thought processes, and employing adaptable problem-solving approaches. Such an environment facilitates the balanced and synergistic development of students' cognitive and affective domains.